Pengembangan Aplikasi Mobile Augmented Reality untuk Pembelajaran Tengkorak Manusia - Muhamad Nasir; Devita Irzal (Buletin Ilmiah Informatika Teknologi, 2023)
Medical is a faculty that studies human anatomy, one of which is the skeleton of human, one of them is the human skull. The skull is one of the appendicular skeleton, currently the media for learning bones still use torso. Along with the development of technology, in this study utilizing Augmented Reality technology as an alternative in studying every part of the skull and to make it easier for students to clearly recognize each skull detail. Besides that, for other purposes this research is to save costs in purchasing torso props. Students who have Android smartphones can easily have a replacement application for human skull torso. The outcomes in this study are: physical form (print media) form of paper called marker and mobile-based augmented reality applications where they complement each other. The results of the tests carried out, the application developed has the potential as an alternative application in the learning process that can assist students in knowing the functions and names of bones..